Mangrove community structure survey in Barangay Guisi and Linayasan, Altavas, Aklan. - Bullo, Gliford G.
The mangrove forest is a complex and unique community of medium to large trees, shrubs, vines and palms, oddly thriving with luxuriant growth in the least inviting habitats which ahve the barest and limited conditions for the growth and survival of higher plant life. This study aims to assess the community structure of mangroves in Barangay Guisi and Linayasan, Aklan using accepted ecological indicators. The sampling site, Altavas Aklan is located at the upper median of Panay Island. There was a total of 15 true mangrove species belonging to the 9 families in the area. The nine families are Family Myrsinaceae represented by Aegiceras corniculatum, Family Avicenniaceae represented by Avicennia alba, Avicennia marina, Avicennia officinalis and Avicennia rumphiana; Family Rhizophoraceae represented by Rhizophora apiculata, Rhizophora mucronata, Bruguiera gymmorhiza and Bruguiera parviflora; Family Bombacaceae represented by Camptostemon philippensis; Family Rubiaceae represented by Scyphiphora hydrophylaceae; Family Meliaceae represented by Xylocarpus granatum and Family Palmae represented by Nypa Fruiticans. Avicennia rumphina has the highest mean basal area of 23.21 (msquared/ha) while Xylocarpus granatum had the lowest mean basal area of 0.01 (msquared/ha). Avicennia rumphiana has the highest relative density of 57 while Xylocarpus granatum has the lowest relative density with a value of 1. Avicennia rumphiana and Avicennia officinalis had the highest relative frequency of 19.8667. Aegiceras corniculatum, Excoecaria agallocha, Scyphiphora hydrophilaceae and Xylocarpus granatum on the other hand had the lowest relative frequency of 0.4. Avicennia rumphiana is the dominant species with a relative dominance value of 23.66 and Xylocarpus granatum is the least dominant species with relative dominance value of 0.01. Avicennia rumphiana is the ,ost important species in the area with an importance value of 127.1816 and the least important species as observed is Xylocarpus granatum with an importance value of 1.685863. The index of diversity is 0.918655 for the entire area.